Factors influencing healthcare-seeking behavior and its process analysis among ethnic minority residents: a qualitative study in rural China - Shu Wei; Haifeng Long; Yu Tian (Frontiers in Public Health)
BackgroundHealthcare-seeking behavior is a crucial foundation for improving the rational use of healthcare resources and enhancing community health. Existing studies have predominantly focused on quantitative analyses of healthcare-seeking choices and their determinants based on the Homo Economicus assumption, while neglecting the analysis of sociocultural processes underlying healthcare-seeking behavior.MethodsThis study employed participant observation and in-depth interviews to investigate thirty-two residents from ethnic minority rural areas, with selected typical cases subjected to focused discussion. Based on the theoretical perspective of social capital, this paper explores and analyzes the healthcare-seeking behavior and its underlying logic in ethnic minority rural areas.ResultsThe findings suggest that institutional trust and interpersonal trust influence patients’ choices between formal and informal medical systems. Medical care information, as a prerequisite for patients’ decisions, flows differently within ethnic relationship networks and community social networks. Institutional and cultural norms collectively influence healthcare service behaviors and provide support for patients’ healthcare-seeking behavior.ConclusionThe adjustment of social medical policy should be guided by the advantages of the formal medical system and the informal medical system, so that the primary medical system can provide high-quality medical services for local residents.